2000
DOI: 10.1076/1388-0209(200007)38:3;1-s;ft192
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel in Combination with Coumarin as a Potentially Effective Anticancer Agent

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Supuran and his group have reported that some of the coumarinylsubstituted benzenesulfonamide series are potent, low nanomolar CA-V inhibitors [26]. In another study, Zobel et al demonstrated the enhanced anticarcinogenic potential of combining coumarin at high concentrations (greater than 10 ppm) with the chemotherapy agent, Paclitaxel [32].…”
Section: Resultsmentioning
confidence: 97%
“…Supuran and his group have reported that some of the coumarinylsubstituted benzenesulfonamide series are potent, low nanomolar CA-V inhibitors [26]. In another study, Zobel et al demonstrated the enhanced anticarcinogenic potential of combining coumarin at high concentrations (greater than 10 ppm) with the chemotherapy agent, Paclitaxel [32].…”
Section: Resultsmentioning
confidence: 97%
“…Zobel and Schellenberger suggested that paclitaxel can be used in combination with other natural products such as coumarins for the inhibition of mitosis. 2 Coumarins are extruded to the surface of many medicinal plants 3 and can cause phytophotodermatitis if psoralens rubbed on the skin are exposed to ultraviolet radiation, either artificial or in sunlight. 4 We have found several interesting taxoids among them paclitaxel, on the surface of Taxus leaves, each potentially toxic.…”
Section: Introductionmentioning
confidence: 99%